A consensus research agenda for optimising nasal drug delivery. (1st February 2020) - Forbes, Ben; Bommer, Rene; Goole, Jonathan; Hellfritzsch, Marie; De Kruijf, Wilbur; Lambert, Pierre; Caivano, Grazia; Regard, Alain; Schiaretti, Francesca; Trenkel, Marie; Vecellio, Laurent; Williams, Gerallt; et al.
ABSTRACT: Nasal drug delivery has specific challenges which are distinct from oral inhalation, alongside which it is often considered. The next generation of nasal products will be required to deliver new classes of molecule, e.g. vaccines, biologics and drugs with action in the brain or sinuses, to local and systemic therapeutic targets. Innovations and new tools/knowledge are required to design products to deliver these therapeutic agents to the right target at the right time in the right patients. We report the outcomes of an expert meeting convened to consider gaps in knowledge and unmet research needs in terms of (i) formulation and devices, (ii) meaningful product characterization and modeling, (iii) opportunities to modify absorption and clearance. Important research questions were identified in the areas of device and formulation innovation, critical quality attributes for different nasal products, development of nasal casts for drug deposition studies, improved experimental models, the use of simulations and nasal delivery in special populations. We offer these questions as a stimulus to research and suggest that they might be addressed most effectively by collaborative research endeavors.